STRATEGIC MANAGEMENT ACCOUNTING PRACTICES: A LITERATURE REVIEW - Husda, Anggun Permata; Rustam, Triana Ananda; Banjarnahor, Haposan (LPPM Universitas Putera Batam, 2025)
Accounting techniques for strategic management incorporate both non-financial and financial data into an organization's strategic decision-making process. Through an examination of the literature, the study seeks to ascertain the practice of strategic management accounting. The balanced scorecard, value chain analysis, and competitive benchmarking are just a few of the frequently utilized strategic management accounting tools and methodologies that are identified in this study. Google Scholar, a significant source of Indonesian scientific publications over the previous ten years, was used in the study's literature analysis to ascertain the use of strategic management accounting. This literature review provides a thorough picture of the development of research on the relationship between strategic management accounting, service quality, knowledge management, and performance by methodically arranging findings, methodology, and concepts chronologically. Optimizing strategic decision-making, resource management, and service quality all depend on the successful integration of strategic management accounting. It is anticipated that the organization will benefit greatly from the synergy between these components. By providing a more thorough understanding of the genesis, advantages, and difficulties of strategic management accounting techniques, this study advances management accounting theory and practice. Empirical investigation of the efficacy of strategic management accounting techniques in various industry and national contexts is one of the recommendations for additional research.